Potensi pengendalian larva nyamuk Aedes aegypti (Linnaeus) dengan menggunakan tiga varietas ikan cupang (Betta splendens): Potential for controlling Aedes aegypti (Linnaeus) mosquito larvae using three varieties of betta fish (Betta splendens) - Adrianto, Hebert; Silitonga, Hanna Tabita Hasianna; Ritunga, Imelda; Santoso, Gianina Angelia; Juwono, Martha Vinda Candra (Perhimpunan Entomologi Indonesia, 2024)
Dengue fever (DF) is a viral disease transmitted by the Aedes aegypti (Linnaeus) mosquito, which has the fastest spreading cases. Drug and vaccines are still unavailable, so the Government is focusing on mosquito control. One method of biological control is to use betta fish (Betta splendens) as predators of Ae. aegypti larvae. Betta fish have various varieties, which may have different abilities in preying on Ae. aegypti larvae. The study aimed to analyze the potential for controlling Ae. aegypti larvae using three varieties of B. splendens fish (multi-colored plakat koi, xanthic morph plakat, and halfmoon varieties) during the day and evening. The test was carried out by inserting 25 Ae. aegypti larvaes into an aquarium containing B. splendens fish. Testing starts at 12.00 and 15.00 WIB and replicated five times. Observations started from the fish started preying on larvae until the fish ate all larvae. The predation ability of each variety of B. splendens fish based on predation time was analyzed using the one-way ANOVA test and the unpaired data t-test. The analysis showed that the multi-colored koi plakat variety preyed Ae. aegypti larvae faster than the xanthic morph plaque variety (P < 0.05) and not significantly different from the halfmoon variety (P > 0.05). There was no difference in the ability of B. splendens fish to prey larvae during the day and evening (P > 0.05). B. splendens fish, the multi-colored koi plaque variety, and the halfmoon variety can be biological predators of Ae. aegypti larvae.